Semaglutide and kidney function: friends or enemies? - Federica Giofrè; Vincenzo Trapanese; Maria Resilde Natale; Clara Vatalaro; Francesca Cosentino; Melania Melina; Maria Chiara Pelle; Nazareno Carullo; Maria Capria; Franco Arturi (Italian Journal of Medicine, 2024)
Semaglutide is a glucagon-like peptide-1 receptor agonist (GLP-1 RAs) approved for the treatment of type 2 diabetes mellitus (T2DM) and chronic weight management in obesity. GLP-1RAs are being investigated to slow the decline of kidney function in type 2 diabetics with chronic kidney disease. These agents prevent renal complications and have proven beneficial effects on cardiac outcomes. We describe a rare case of semaglutide-induced acute kidney injury (AKI) in a young woman with obesity, T2DM, hypertensive cardiomyopathy, and no pre-existing chronic kidney disease (CKD). This case is relevant as GLP1-RAs is used frequently in patients with and without kidney disease. Currently, only 3 cases of AKI ascribed to semaglutide of which only 1 without CKD have been described. Only in this case, kidney function improves after semaglutide discontinuation. However, because GLP1-RAs will be prescribed more and more frequently, we sought to highlight this possible, serious adverse effect of semaglutide.